Retextualização do gênero textual histórias em quadrinhos e a produção escrita na Educação de Jovens e Adultos (EJA) - Segato, Wagner Antonio (2024)
This dissertation presents the process of retextualization (Marcushi 2010a), addressing both orality and writing for the production of texts at school. In it, we outline a brief history of EJA based on Aranha, 2006, Piletti and Piletti, 1986a, Piletti, 1986b, Jardilino and Araújo, 2014. Likewise, they are involved in this alignment in the process from speaking to writing through of retextualization, the works of Dell'Isola, 2007; Ribeiro and Coscarelli, 2023; Ribeiro, 2016 and Cobucci and Machado, 2023. The genres and textual types that are highlighted in the relationship of the continuum between orality and writing are also presented. They are four types: speech-writing, writing-writing, writing-speech, speech-speech (Marcuschi, 2010a, 2010b, 2008, 2007; Bezerra, 2022; PCN, 1998; Koch and Elias, 2011a, 2011b) and their models of retextualization operations. There is not only retextualization in the relationship between speech and writing in the production of texts so that students produce written texts, but the elements of the narrative and the types of balloons that enable the transition from speech to writing are also presented (Faraco and Moura, 1995 ; Gancho, 2006; When reading comic books, we find types of discourse, direct and indirect, and also their reading narratives that make it possible to propose retextualization activities. In this way, students produce their new text, introducing indirect speech and (re)creating their formulations in the construction of this text, in which cohesion, coherence, spelling, punctuation and, mainly, textual organization are analyzed. between the beginning, the middle and the end